Simulation Based Comparison Between OWL and DSDV. (2016) - Swami, Balram; Singh, Ravindar
Abstract: Mobile ad-hoc network is collection of mobile nodes like laptops; cell phones which have limited processing power and limited battery power also have limited bandwidth. MANET is self-adjustable with dynamic topology network, because of its mobile environment, routing face challenges. Main challenges in routing are to maximize delivery ratio and minimize End-to-End delay with minimum use of nodes resources, because mobile nodes have limited batter power and bandwidth. DSDV is proactive type routing protocol which trying to minimize route discovery time by manage route information in routing table and broadcast to other neighbors. OWL is a reactive routing protocol which uses DFS instead of broadcasting of RREQ to all its neighbors. In this paper we are going to compare these two routing protocol on the basis of their power consumption in different phases of routing.